2023
DOI: 10.1038/s41598-023-32382-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genetic characterization of porcine circovirus 4 (PCV4) in Thailand during 2019–2020

Abstract: Porcine circovirus 4 (PCV4) is considered a novel PCV, firstly found in China in 2019 and later discovered in Korea. This present study investigated the prevalence and genetic characteristics of PCV4 from high pig-density areas in Thailand during 2019–2020. From 734 samples, three samples (0.4%) from aborted fetuses and porcine respiratory disease complex (PRDC) cases were found positive for PCV4, two of the PCV4-positive samples were coinfected with both PCV2 and PRRSV, and the other PCV4-positive sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…PCV4 was first registered in China in 2019 ( 23 ). Since then, this novel virus has been detected in domestic pigs in Thailand ( 24 ), South Korea ( 25 ), and more recently, in wild boars and domestic pigs in Europe ( 26 ). Simultaneously, its pathogenicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PCV4 was first registered in China in 2019 ( 23 ). Since then, this novel virus has been detected in domestic pigs in Thailand ( 24 ), South Korea ( 25 ), and more recently, in wild boars and domestic pigs in Europe ( 26 ). Simultaneously, its pathogenicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PCV-4 DNA has been detected in other domestic species such as dairy cows and dogs in China [ 5 , 6 ]. Outside China, PCV-4 genome has been found only in Korea and Thailand [ 7 , 8 ], although several surveys have been conducted in other continents, such as South America and Europe [ 9 , 10 ]. Therefore, Asia is the only continent where the virus has been detected so far.…”
Section: Introductionmentioning
confidence: 99%
“…The limited sequences available point out the existence of two different genotypes of PCV-4 (PCV-4a and PCV-4b). Both genotypes have been found in China, although only the PCV-4b one has been identified in Thailand and South Korea [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful isolations of PCV3 as well as pathogenicity demonstration through infectious molecular clones have been reported (Jiang et al, 2019;Mora-D‫ם‬az et al, 2020;Oh & Chae, 2020). Most recently, yet another new species was identified in China, South Korea and Thailand, sequentially named porcine circovirus 4 (PCV4) (Zhang et al, 2020;Nguyen et al, 2022;Sirisereewan et al, 2023). Infectious clone of PCV4 had been shown to induce systemic pathological changes in piglets (Niu et al, 2022) In Malaysia, PCV2 with its myriad of PCVAD has been reported to be endemic in the local pig farming industry since its first detection (Hassuzana et al, 2004).…”
Section: Introductionmentioning
confidence: 99%